Method for preparing high-defect coal pitch-based porous carbon through in-situ oxidation-carbonization in air
By using an in-situ oxidation-carbonization method with a montmorillonite template in an air atmosphere, the preparation process is simplified, solving the problems of cumbersome processes and resource waste in the existing technology. High-defect coal tar pitch-based porous carbon is prepared, which improves the performance of zinc ion hybrid capacitors.
Patent Information
- Application Number
- CN202511617736.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-06
- Publication Date
- 2026-01-23
AI Technical Summary
Existing technologies for preparing zinc-ion hybrid capacitor cathode materials suffer from cumbersome processes and reduced effectiveness, especially the resource waste and high cost caused by carbonization under an inert atmosphere.
The preparation process is simplified by using in-situ oxidation-carbonization in air atmosphere and inexpensive two-dimensional montmorillonite as a template. The oxygen is diluted by the interlayer bound water of montmorillonite, which inhibits the excessive combustion of coal tar pitch and forms highly defective coal tar pitch-based porous carbon during the carbonization process.
This method enables efficient and convenient preparation of porous carbon based on high-defect coal tar pitch, improving the electrochemical performance of zinc-ion hybrid capacitors. These capacitors exhibit high specific capacitance and excellent commercial value, making them suitable for industrial production.
Smart Images

Figure CN121394187A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the field of preparation of high-performance zinc ion hybrid capacitor positive electrode materials, and particularly relates to a method for preparing high-defect coal pitch porous carbon by in-situ oxidation-carbonization under an air atmosphere based on a flame-retardant principle. BACKGROUND
[0002] In modern times, with the overexploitation and utilization of non-renewable energy sources such as fossil fuels, mankind is facing two major problems of energy crisis and environmental pollution, and vigorously developing green and clean sustainable energy is one of the important ways to solve the problem. Among them, zinc ion hybrid capacitors, as an important energy storage device, have the characteristics of both supercapacitors' fast charging and discharging ability and zinc ion batteries' high energy density, and have attracted widespread attention and research in recent years. Zinc ion hybrid capacitors store energy through the redox reaction of the zinc negative electrode and the double-layer / pseudocapacitance behavior of the porous carbon positive electrode. Among them, the defect density, pore structure and surface functional groups of the porous carbon positive electrode material will directly affect the performance of the zinc ion hybrid capacitor.
[0003] Coal tar pitch is the final product of coal tar distillation, and is an ideal precursor for preparing advanced carbon materials due to its high carbon content and unique molecular structure. Microscopically, coal tar pitch is a complex multiphase system mainly composed of interwoven polycyclic aromatic hydrocarbons and a small amount of macromolecular substances. This structural heterogeneity at the molecular level endows coal tar pitch with unique rheological properties and adjustable carbonization behavior. However, during the carbonization process in an inert atmosphere, coal tar pitch will undergo liquid-phase carbonization, and the strong π-π interaction between polycyclic aromatic hydrocarbons promotes the formation of highly graphitized carbon. Although this structure enhances the graphitization order, it limits the defect sites and transport paths accessible to ions, thereby hindering the adsorption / desorption kinetics of ions. Air pre-oxidation is one of the most commonly used methods for preparing high-defect coal pitch porous carbon. Patent Publication No. CN119612513A discloses a preparation method and application of coal pitch-based porous carbon. The coal pitch-based porous carbon is prepared by a stepwise oxidation-carbonization method of pre-oxidation in air combined with carbonization, and the preparation process is complicated and the operation is complex. Patent Publication No. CN119330354A discloses a preparation method and application of high-performance pitch-based porous carbon material. First, the pitch raw material is heat-treated, and then a method combining pre-oxidation and carbonization is used to prepare an electrode material for supercapacitors, but the process is too complicated. The above methods all have a complex multi-step process (pre-oxidation-carbonization), and the defect effect is weakened due to the thermal decomposition of oxygen-containing functional groups. Therefore, developing an in-situ oxidation-carbonization method for preparing coal pitch porous carbon under an air atmosphere is a very promising approach.
[0004] The high-temperature carbonization combustion of carbon precursors in an air atmosphere will cause serious mass loss. By adding montmorillonite natural minerals to the carbon precursors, the release of interlayer combined water of montmorillonite can dilute the combustible gas concentration and cooperate with the functions of the template and activation, thereby providing an effective way for the preparation of porous carbon materials in an air atmosphere. The two-dimensional montmorillonite natural layered minerals have smooth surfaces and often contain nanometer spaces between the layers, which can not only provide storage space for the insertion and adsorption of carbon precursor molecules, but also act as a nano-reactor to provide a confined space for the subsequent pyrolysis and polymerization reactions of carbon precursors, thereby strengthening the directional conversion of carbon precursors into two-dimensional carbon materials such as carbon nanosheets. SUMMARY
[0005] To overcome the shortcomings of the prior art, the purpose of the present application is to provide a method for preparing high-defect coal pitch-based porous carbon by in-situ oxidation-carbonization in air, which simplifies the carbonization step and reduces resources and costs. The cheap two-dimensional montmorillonite is used to prepare coal pitch-based porous carbon with high defects in an air atmosphere, and the material is applied to zinc ion hybrid capacitors. The synthesis of the material utilizes the template functionalization of montmorillonite to prepare high-defect, high-yield coal pitch-based porous carbon by in-situ oxidation-carbonization in an air atmosphere.
[0006] To achieve the above-mentioned purpose, the present application realizes the following technical solutions:
[0007] A method for preparing high-defect coal pitch-based porous carbon by in-situ oxidation-carbonization in air, comprising the following steps:
[0008] 1) Take coal pitch and two-dimensional natural minerals;
[0009] 2) Grind the coal pitch and two-dimensional natural minerals to mix them evenly;
[0010] 3) Put the mixture obtained in step 2) into a muffle furnace for in-situ oxidation-carbonization;
[0011] 4) Perform chemical cleaning, water washing and drying on the carbonized product to obtain high-defect coal pitch-based porous carbon.
[0012] The coal pitch is one or more of low-temperature coal tar pitch, medium-temperature coal tar pitch, high-temperature coal tar pitch and impregnant coal pitch.
[0013] The mass ratio of montmorillonite to coal pitch is 2:1 to 8:1.
[0014] In step 2), the grinding is performed by one or more of a ball mill, a mortar and a vibration grinder.
[0015] In step 2), the grinding time is 30 to 60 minutes.
[0016] Step 2) the particle size of the ground product is 0.01-0.1 mm.
[0017] In step 3), the mixture is placed in a muffle furnace and in-situ carbonization is carried out at a temperature of 600-1000℃ at a temperature increasing rate of 3-5℃ / min, and the holding time is 1-3h.
[0018] In step 4), the chemical cleaning agent is one or more of 40wt%-60wt% hydrofluoric acid, 20wt%-40wt% sodium hydroxide solution and 20wt%-30wt% potassium hydroxide solution.
[0019] The amount of the chemical cleaning agent used in step 4) is 10-30mL.
[0020] The drying in step 4) is drying at 80-120℃ for 8-16h.
[0021] Compared with the prior art, the present application has the following advantages:
[0022] 1. The present application discards the traditional complicated "pre-oxidation-carbonization" multi-step process and realizes the "in-situ oxidation-carbonization" one-step synthesis in air atmosphere. No mixed acid or air pre-oxidation pretreatment is needed, which significantly simplifies the preparation steps and makes the operation more simple.
[0023] 2. The present application prepares porous carbon in air, which utilizes the flame retardant property of natural minerals, especially the dilution of oxygen by the interlayer combined water volatilized at high temperature, effectively inhibits the excessive combustion and mass loss of coal pitch in air, and ensures a certain carbon yield. The in-situ oxidation in air atmosphere endows the coal pitch with a large number of oxygen-containing functional groups. These functional groups can react with the active hydrogen of polycyclic aromatic hydrocarbons in the subsequent carbonization, weakening the polycondensation of polycyclic aromatic hydrocarbons, thereby inhibiting the formation of highly graphitized carbon and improving the defect density of the material. The use of the templating and limiting function of montmorillonite makes the coal pitch molecules grow and polymerize along the layered structure, and finally obtains two-dimensional sheet-shaped porous carbon. This structure is beneficial to the transmission and storage of ions.
[0024] 3. The present application uses cheap and abundant two-dimensional natural mineral montmorillonite as a template, and the raw material is easy to obtain. The method uses high, medium and low temperature and impregnating agent, etc. various coal pitch, realizes the high value-added utilization of coal chemical by-products, has high economic benefit, and the preparation process is simple, easy to operate and control, and has the potential of industrial production.
[0025] 4. The high-defect coal pitch-based porous carbon prepared by the present application can be used as an electrochemically active site, which significantly improves the performance of the high-defect coal pitch-based porous carbon as a positive electrode material in a zinc ion hybrid capacitor. When the high-defect coal pitch-based porous carbon is used as a positive electrode material in a zinc ion hybrid capacitor, it exhibits high specific capacity and excellent electrochemical performance and commercial value. Attached Figure Description
[0026] Figure 1 This is a SEM image of the highly defective coal tar pitch-based porous carbon prepared in Example 1.
[0027] Figure 2 This is a SEM image of the high-defect coal tar pitch-based porous carbon prepared in Example 2.
[0028] Figure 3 This is a SEM image of the highly defective coal tar pitch-based porous carbon prepared in Example 3.
[0029] Figure 4 This is a SEM image of the highly defective coal tar pitch-based porous carbon prepared in Example 4.
[0030] Figure 5 These are the XRD patterns of Examples 1-4.
[0031] Figure 6 These are the Raman spectra of Examples 1-4.
[0032] Figure 7 These are GCD curves of Examples 1-4 in 6MKOH.
[0033] Figure 8 This is a charge-discharge curve of a zinc-ion hybrid capacitor. Detailed Implementation
[0034] To further understand the present invention, the present invention will be described below with reference to embodiments. These descriptions are only for further explaining the features and advantages of the present invention and are not limited to the following embodiments.
[0035] Example 1:
[0036] A method for preparing high-defect coal tar pitch-based porous carbon through in-situ oxidation-carbonization in air:
[0037] 0.2 g of impregnating agent coal tar pitch and 0.4 g of montmorillonite as a functionalizing agent were weighed and ground thoroughly in a ball mill for 60 min until uniformly mixed with a particle size of 0.01 mm. The mixture was placed in a crucible and heated to 700 °C in a muffle furnace under air atmosphere at a heating rate of 5 °C / min for high-temperature carbonization, held at that temperature for 1 hour, and then allowed to cool naturally to room temperature. 10 ml of 40 wt% hydrofluoric acid was added to the mixture and stirred for 12 h to remove montmorillonite, followed by washing with water until neutral. The mixture was then dried in an oven at 80 °C for 12 h to obtain the final product. The final yield was 41.2%. To compare the advantages of the air in-situ oxidation carbonization method, impregnating agent coal tar pitch-based porous carbon was prepared by the same method under a nitrogen atmosphere.
[0038] like Figure 1As shown, the carbon material prepared in Example 1 exhibits a two-dimensional sheet-like structure. Figure 5 As shown, broad diffraction peaks appear near the 23° (002) and 43° (101) crystal planes, indicating the presence of an amorphous carbon structure. Figure 6 As shown, compared with carbon materials prepared under a nitrogen atmosphere (I D / I G =0.81), carbon materials prepared in an air atmosphere have higher defects (I D / I G =0.92). Electrode materials were prepared by mixing the coal tar pitch-based high-defect porous carbon material prepared in this embodiment with Ketjen black and polyvinylidene fluoride at a mass ratio of 8:1:1. The electrochemical performance of the three-electrode and zinc-ion hybrid capacitors was tested in a CHI760 and Blue Battery testing system, respectively. The sample prepared under air atmosphere achieved a specific capacitance of 303 F / g, see [reference needed]. Figure 7 In zinc-ion hybrid capacitors, a specific capacitance of 164 mAh / g can be achieved, see [reference needed]. Figure 8 .
[0039] Example 2:
[0040] A method for preparing high-defect coal tar pitch-based porous carbon through in-situ oxidation-carbonization in air:
[0041] 0.2 g of high-temperature coal tar pitch and 0.4 g of montmorillonite as a functionalizing agent were weighed and ground thoroughly in an agate mortar for 30 min to a particle size of 0.1 mm. The mixture was placed in a crucible and heated to 700 °C in a muffle furnace under air atmosphere at a heating rate of 5 °C / min for high-temperature carbonization, held at that temperature for 1 hour, and then allowed to cool naturally to room temperature. 20 ml of a 30 wt% sodium hydroxide solution was added to the mixture and stirred for 12 h to remove the montmorillonite, followed by washing with water until neutral. The mixture was then dried in an oven at 80 °C for 12 h to obtain the final product. The final yield was 45.6%. To compare the advantages of the in-situ air oxidation carbonization method, high-temperature coal tar pitch-based porous carbon was prepared using the same method under a nitrogen atmosphere.
[0042] like Figure 2 As shown, the carbon material prepared in Example 2 exhibits a two-dimensional sheet-like structure. Figure 5 As shown, broad diffraction peaks appear near 23° and 43°, indicating the presence of an amorphous carbon structure. Figure 6 As shown, Raman results indicate that compared to carbon materials prepared under a nitrogen atmosphere (I... D / I G =0.82), carbon materials prepared in an air atmosphere have higher defects (I D / I G=0.87). Electrode materials were prepared by mixing the coal tar pitch-based high-defect porous carbon material prepared in this embodiment with Ketjen black and polyvinylidene fluoride at a mass ratio of 8:1:1. The electrochemical performance of the three-electrode and zinc-ion hybrid capacitors was tested in a CHI760 and Blue Battery testing system, respectively. The sample prepared under air atmosphere achieved a specific capacitance of 201 F / g, see [reference needed]. Figure 7 In zinc-ion hybrid capacitors, a specific capacitance of 125 mAh / g can be achieved, see [reference needed]. Figure 8 .
[0043] Example 3:
[0044] A method for preparing high-defect coal tar pitch-based porous carbon through in-situ oxidation-carbonization in air:
[0045] 0.2 g of medium-temperature coal tar pitch and 0.5 g of montmorillonite as a functionalizing agent were weighed and ground thoroughly in an agate mortar for 30 min to a particle size of 0.1 mm. The mixture was placed in a crucible and heated to 700 °C in a muffle furnace under air atmosphere at a heating rate of 5 °C / min for high-temperature carbonization, held at that temperature for 1 hour, and then allowed to cool naturally to room temperature. 15 ml of 40 wt% hydrofluoric acid was added to the mixture and stirred for 12 h to remove the montmorillonite, followed by washing with water until neutral. The mixture was then dried in an oven at 80 °C for 12 h to obtain the final product. The final yield was 41.9%. To compare the advantages of the in-situ air oxidation carbonization method, high-temperature coal tar pitch-based porous carbon was prepared using the same method under a nitrogen atmosphere.
[0046] like Figure 3 As shown, the carbon material prepared in Example 3 exhibits a two-dimensional sheet-like structure. Figure 5 As shown, it exhibits broad diffraction peaks near 23° and 43°, indicating the presence of an amorphous carbon structure. Figure 6 As shown, Raman results indicate that compared to carbon materials prepared under a nitrogen atmosphere (I... D / I G =0.88), carbon materials prepared in an air atmosphere have higher defects (I D / I G =1.06). Electrode materials were prepared by mixing the coal tar pitch-based high-defect porous carbon material prepared in this embodiment with Ketjen black and polyvinylidene fluoride in a mass ratio of 8:1:1. The electrochemical performance of the three-electrode and zinc-ion hybrid capacitors was tested in a CHI760 and Blue Battery testing system, respectively. The sample prepared under air atmosphere achieved a specific capacitance of 221 F / g, see [reference needed]. Figure 7 In zinc-ion hybrid capacitors, a specific capacitance of 124 mAh / g can be achieved, see [reference needed]. Figure 8 .
[0047] Example 4:
[0048] A method for preparing high-defect coal tar pitch-based porous carbon through in-situ oxidation-carbonization in air:
[0049] 0.2 g of low-temperature coal tar pitch and 0.6 g of montmorillonite as a functionalizing agent were weighed and ground thoroughly in an agate mortar for 40 min to a particle size of 0.1 mm. The mixture was placed in a crucible and heated to 700 °C in a muffle furnace under air atmosphere at a heating rate of 5 °C / min for high-temperature carbonization. The mixture was held at this temperature for 1 hour, allowed to cool naturally to room temperature, and then removed. 30 ml of a 30 wt% potassium hydroxide solution was added to the mixture and stirred for 12 h to remove the montmorillonite. The mixture was then washed with water until neutral. Finally, it was dried in an oven at 80 °C for 12 h to obtain the final product. The final yield was 39.5%. To compare the advantages of the in-situ air oxidation carbonization method, low-temperature coal tar pitch-based porous carbon was prepared using the same method under a nitrogen atmosphere.
[0050] like Figure 4 As shown, the carbon material prepared in Example 4 exhibits a two-dimensional sheet-like structure. Figure 5 As shown, its XRD pattern exhibits broad diffraction peaks near 23° and 43°, indicating the presence of an amorphous carbon structure. Figure 6 As shown, Raman results indicate that compared to carbon materials prepared under a nitrogen atmosphere (I... D / I G =0.85), carbon materials prepared in an air atmosphere have higher defects (I D / I G =0.93). Electrode materials were prepared by mixing the coal tar pitch-based high-defect porous carbon material prepared in this embodiment with Ketjen black and polyvinylidene fluoride at a mass ratio of 8:1:1. The electrochemical performance of the three-electrode and zinc-ion hybrid capacitors was tested in a CHI760 and Blue Battery testing system, respectively. The sample prepared under air atmosphere achieved a specific capacitance of 291 F / g, see [reference needed]. Figure 7 In zinc-ion hybrid capacitors, a specific capacitance of 143 mAh / g can be achieved, see [reference needed]. Figure 8 .
[0051] The porous carbon material prepared by this invention exhibits high yield and high defect density, achieving a specific capacitance of 200–305 F / g as a positive electrode material for zinc-ion mixed capacitors, and demonstrating excellent specific capacitance of 120–170 mAh / g. This method differs from traditional inert atmosphere-protected carbon material preparation methods, reducing costs and resource consumption. It is a green, simple, economical, efficient, and controllable preparation method. Furthermore, this preparation method is simple to operate and has a short synthesis cycle, making it suitable for large-scale industrial production. This method has significant implications for the preparation and application of high-performance porous carbon electrode materials.
Claims
1. A method for the in-situ oxidative-carbomzation of high defect coal pitch-based porous carbon in air, characterized in that, The method comprises the following steps: 1) taking coal pitch and two-dimensional natural mineral; 2) grinding the coal pitch and two-dimensional natural mineral to mix them evenly; 3) placing the mixture obtained in step 2) in a muffle furnace to perform in-situ oxidation carbonization; 4) performing chemical cleaning, water washing and drying on the carbonized product to obtain high-defect coal pitch-based porous carbon.
2. A process for in-situ oxidation-carbonization of coal-tar pitch based porous carbon with high defects in air as claimed in claim 1, wherein, The coal pitch is one or more of low-temperature coal tar pitch, medium-temperature coal tar pitch, high-temperature coal tar pitch and impregnant coal pitch.
3. A process for in-situ oxidation-carbonization of coal-tar pitch based porous carbon with high defects in air as claimed in claim 1, wherein, The mass ratio of the montmorillonite to the coal pitch is 2:1 to 8:
1.
4. A process for in-situ oxidation-carbonization of coal-tar pitch based porous carbon with high defects in air as claimed in claim 1 wherein, The grinding in step 2) is performed by using one or more of a ball mill, a mortar and a vibration grinder.
5. A process for in-situ oxidation-carbonization of coal-tar pitch based porous carbon with high defects in air as claimed in claim 1, wherein, The grinding in step 2) is performed for 30 to 60 min.
6. A process for in-situ oxidation-carbonization of coal-tar pitch based porous carbon with high defects in air as claimed in claim 1, wherein, The particle size of the product after the grinding in step 2) is 0.01 to 0.1 mm.
7. A method of in-situ oxidation-carbonization of coal-tar pitch based porous carbon with high defects in air according to claim 1, characterized in that, In step 3), the mixture is placed in a muffle furnace, heated to 600 to 1000 ℃ at a heating rate of 3 to 5 ℃ / min, and kept for 1 to 3 h for in-situ oxidation carbonization.
8. A process for in-situ oxidation-carbonization of coal-tar pitch based porous carbon with high defects in air as claimed in claim 1, wherein, The chemical cleaning in step 4) is performed by using one or more of 40wt% to 60wt% hydrofluoric acid, 20wt% to 40wt% sodium hydroxide solution and 20wt% to 30wt% potassium hydroxide solution.
9. A process for in-situ oxidation-carbonization of coal-tar pitch based porous carbon with high defects in air as claimed in claim 1, wherein, The amount of the chemical cleaning reagent in step 4) is 10 to 30 mL.
10. A process for in-situ oxidation-carbonization of coal-tar pitch based porous carbon with high defects in air as claimed in claim 1 wherein, The drying in step 4) is performed at 80 to 120 ℃ for 8 to 16 h.
Citation Information
Patent Citations
Preparation and application of high-performance asphalt-based porous carbon material
CN119330354A
Preparation method and application of coal pitch-based porous carbon
CN119612513A